A simple rotational spring model for laterally loaded rigid piles in sand. (July 2022) - Wang, H.; Lehane, B.M.; Bransby, M.F.; Askarinejad, A.; Wang, L.Z.; Hong, Y.
Abstract: Monopiles are the most popular foundation for offshore wind turbines. These foundations typically have a low length to diameter ratio and undergo a rigid body rotation when subjected to lateral load. This paper presents results from an extensive numerical investigation involving 3D finite element analyses to demonstrate that the lateral moment-rotation response of a monopile in sand can be represented using a single non-linear rotational spring located at a depth of about 0.75 times the pile embedment. Expressions for the elastic rotational stiffness of a monopile under very low rotations are developed and these combined with observations from measured non-linear variations of rotational stiffness, that are supported by the numerical analyses, are used to develop a simple approximate expression that can be used to determine the response of a monopile to a monotonic lateral load in sand. Highlights: An extensive 3D finite element analyses of the laterally monopile in sand was performed using the advanced hypoplastic model for sand. A single non-linear rotational spring located at rotation centre, i.e. 0.75 times the pile embedment, was proposed to model the lateral response of monopile. Expressions for the elastic response of a monopile under very low rotations are developed. Based on observations from measured non-linear variations of rotational stiffness and the numerical analyses, a simple approximate expression was developed to determine the response of a monopile to a monotonic lateral load in sand.